The role of trip generation models in sustainable transportation planning in South-East Europe - Jović, Jadranka; Depolo, Vladimir (Transport, 2011)
The idea, representing a fundamental starting point in this article, is to confirm that the models for demand forecasting, in terms of planning urban development, gave the results of the forecasted period. In other words, the available models continue to be a valid theoretical basis to be used for planning the sustainable development of the cities. The presentation of model development in the cities of South-East Europe shows that the matter of city sustain-ability has always represented the focus of attention and has been the subject since the early ‘50s till the present day. Modelling trip generation in transportation studies in the cities of the former Yugoslavia has been taken as the basis for this paper, because it reflects all the stages modelling went through. Such situation was strongly influenced by foreign experience, especially that gained by Anglo-Saxons. Introducing procedures for analytical modelling that relate household socio-economic and land use characteristics to the intensity of land use represented the pioneering step in procedures for integral land use, activity intensity and transportation demand planning. In the cities of South-East Europe, all known methods of trip generation modelling were applied in transportation planning practice. Recently, Serbian researchers have acknowledged that the process of balancing demand for mobility resulting from the purpose, activity intensity and supply to the transportation system (infrastructure and services) terminates in forming the ‘fields of improved accessibility’ (i.e. the parts of the urban area more influenced by investments). The process of forming them causes ‘pressure’ to increase activity intensity (appearance is known as induced construction) that ends in inducing new demand. In this context, there are efforts to integrate trip generation models into ones of spatial distribution taking into consideration the above described conditions and creating the basis for balanced and sustainable development of the cities. First Published Online: 12 Apr 2011